Chipless tag detection and recognition based on frequency modulated continuous wave. Issue 1 (July 2021) - Zhang, Qianglin; Zou, Chuanyun; Jiao, Liangyu
Abstract: Towards the commercialization of chipless radio frequency identification (RFID) systems, there are still some pressing issues. The detection and identification of chipless RFID tags are mainly realized by a vector network analyzer (VNA). In practice, this equipment is costly and not convenient enough. This paper designs a maneuverable detection model based on frequency modulated continuous wave (FMCW), the detection target is an 8-bit chipless tag based on a variable-side-length spiral resonance unit and decodes the amplitude and phase information. On this basis, signal processing is performed on the generated amplitude and phase based on the Savitzky-Golay (SG) smoothing algorithm, and then the simulation data of HFSS is compared with ADS model data by the matrix pencil method (MPM). The results show that the proposed FMCW-based method can be effectively implemented in wireless communication, providing a new solution for flexible and inexpensive chipless tag detection and recognition.